Reba : my story - McEntire, Reba.; Carter, Tom, 1947- (New York, NY Bantam Books, 1994)
Here, for the first time, in her own words - and with more than 140 personally selected family photos - she shares the memories that have shaped and inspired her life and her music. Reba writes with deep pride about the enduring values she learned growing up in the hardworking rodeo and ranching McEntire family in Chockie, Oklahoma. A third-generation rodeo brat, Reba was increasingly drawn toward singing. "This little red-headed girl started singing, and it just blew me away." That was a typical comment when teenage Reba McEntire first started performing. Hers was the hardest of career paths: night after night of VFW halls, honky-tonks, fair shows, and holes-in-the-wall where dances were more like fistfights set to music
Keywords: McEntire, Reba; Country muscians -- Biography -- United States